Effectiveness of Social Work Sanction as a Substitute for Imprisonment in The Perspective of Sentencing Purposes - Emaliawati Emaliawati; Bonarsius Saragih; Aji Mulyana (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
ABSTRACTImprisonment is a criminal sanction that eliminates the freedom of perpetrators with the aim of providing a deterrent effect so as not to commit criminal acts and improve behavior in order to become better human beings. In this study, problems were formulated regarding the effectiveness of social work sanctions as a substitute for imprisonment from the perspective of sentencing purposes. This study uses a normative juridical approach, with descriptive-analytical research specifications. The data used are primary data obtained through an analytical study of applicable laws, followed by concepts that have been carried out, and secondary data obtained through literature studies (references from various countries that have imposed social work sanctions), which are then analyzed utilizing a comparison between primary and secondary data qualitatively. From the study results the issue regarding the effectiveness of social work sanction as a substitute for imprisonment focuses on changing the behavior of the convict in reducing the level of crime in society and the effectiveness of social work punishment for criminals associated with the purpose of sentencing, it is used as an alternative for sentencing that is in line with the purpose of sentencing itself.